Information technology of psychophysiological selection of candidates for contract work - Злепко, Сергій Макарович; Петренко, Володимир Віталійович; Коваль, Леонід Григорович; Тимчик, Сергій Васильович; Гаврілова, Наталя Михайлівна (Eastern-European Journal of Enterprise Technologies, 2012)
The list of problems that must be solved by the complex for psychophysiological selection has defined. Description of testing technology has conducted. Composition of test complex and list of test methods has defined